Grade R teachers’ perceptions concerning parental participation in early literacy development in a disadvantaged context in the Western Cape - Naseema Shaik (Perspectives in Education, 2023)
Parent participation is fundamental to children’s early literacy development and later academic success. This small-scale qualitative study located in the interpretivist paradigm utilised semistructured interviews to collect data from two Grade R teachers’ concerning their perceptions of parent participation in children’s early literacy development. Findings revealed that teachers had a narrow and limiting understanding concerning parental involvement. Teachers attested to parents not being interested in their children’s early literacy due to their socio-economic positions which hurdled their commitments to work. Teachers wanted parents to participate in storytelling but on their terms. These findings have important implications for how policy and practice need to be reconceptualised for a stronger focus on parental participation in children’s early literacy and holistic parental participation.